Synthesis of a cyclic urea as a nonnatural biopolymer scaffold - Kim, JM; Wilson, TE; Norman, TC; Schultz, PG (PERGAMON-ELSEVIER SCIENCE LTD, 1996)
A cyclic urea trimer was synthesized from readily available amino acid derivatives using a simple, iterative approach. A selective amide reduction using borane (BH3-THF) and a triphosgens-mediated cyclization are the key features in a synthesis of the cyclic urea trimer 2. Copyright (C) 1996 Elsevier Science Ltd
Keywords: PEPTIDE COMBINATORIAL LIBRARIES; VINYLOGOUS SULFONYL PEPTIDES; SOLID-PHASE SYNTHESIS; UNNATURAL BIOPOLYMERS; DRUG DISCOVERY